Case Report: Novel Mutation of F5 With Maternal Uniparental Disomy Causes Severe Congenital Factor V Deficiency - Lin Cheng; Ying Li; Wenjuan Zhou; Tao Bo (Frontiers Media S.A., 2022)
We summarized two cases of congenital factor V deficiency (FVD) associated with a novel F5 mutation, and analyzed the relationship of the clinical features and genetic characteristics in congenital FVD. Case 1 was a female newborn infant with remarkable bleeding who died of severe intracranial hemorrhage on day 42 after birth. She had significant prolongation of prothrombin time (PT) and activated partial thromboplastin time (APTT). The percentage activity of FV (PFV) was lower than 3% in case 1. The mother of case 1 showed no tendency to bleed. She had mild prolongation of PT and APTT. The PFV was only 43%. Both cases were found to have the same novel mutation in F5, which was c.5419G>A (p.Ala1807Thr) in exon 16. The variant in case 1 was inherited from the mother of case 1. Whole-exome sequencing (WES) also found a splice site mutation: a 103 Mb maternal uniparental disomy (UPD) of 1q21.1-qter in case 1, in which the F5 gene is located in this segment. So case 1 was homozygote and the mother of case 1 was heterozygote. The novel mutation of F5 was predicted to be harmful by bioinformatics software including Sorting Intolerant From Tolerant (SIFT), Polyphen2, LRT, and Mutation Taster. In summary, c.5419G>A (p.Ala1807Thr) in exon 16 of F5 is a pathogenic mutation, which causes severe congenital FVD in homozygote patients.